Differences in neural and cognitive response to emotional faces in middle-aged dizygotic twins at familial risk of depression. Issue 13 (11th April 2017) - Miskowiak, K. W.; Svendsen, A. M. B.; Harmer, C. J.; Elliott, R.; Macoveanu, J.; Siebner, H. R.; Kessing, L. V.; Vinberg, M.
Abstract : Background: Negative bias and aberrant neural processing of emotional faces are trait-marks of depression but findings in healthy high-risk groups are conflicting. Methods: Healthy middle-aged dizygotic twins ( N = 42) underwent functional magnetic resonance imaging (fMRI): 22 twins had a co-twin history of depression (high-risk) and 20 were without co-twin history of depression (low-risk). During fMRI, participants viewed fearful and happy faces while performing a gender discrimination task. After the scan, they were given a faces dot-probe task, a facial expression recognition task and questionnaires assessing mood, personality traits and coping. Results: Unexpectedly, high-risk twins showed reduced fear vigilance and lower recognition of fear and happiness relative to low-risk twins. During face processing in the scanner, high-risk twins displayed distinct negative functional coupling between the amygdala and ventral prefrontal cortex and pregenual anterior cingulate. This was accompanied by greater fear-specific fronto-temporal response and reduced fronto-occipital response to all emotional faces relative to baseline. The risk groups showed no differences in mood, subjective state or coping. Conclusions: Less susceptibility to fearful faces and negative cortico-limbic coupling during emotional face processing may reflect neurocognitive compensatory mechanisms in middle-aged dizygotic twins who remain healthy despite their familial risk of depression.